Eksplorasi Dampak Strategi Pembelajaran Multimodal Terhadap Pemerolehan Bahasa Bagi Pelajar EFL - A Kamariah; Citra Dwi Safitri; Nurul Ilmi Sudirman; Muhammad Fahri Jaya Sudding; Musdalifah (IEC: Journal of Educational Innovation, 2026)
This article investigates how multimodal learning strategies shape language acquisition among second-semester EFL students in an Applied English Study Program at a public university in Indonesia. Using a qualitative exploratory design, the study examines students’ experiences, responses, and language development during English lessons that systematically integrate texts, images, audio, videos, slides, classroom discussions, gestures, and digital platforms. Data were gathered through classroom observations, semi-structured interviews, documentation, and analysis of students’ learning tasks, then analyzed thematically to identify patterns of change in comprehension and production. The results show that multimodal learning strategies enhance input comprehension, vocabulary growth, oral and written production, learning engagement, communicative interaction, and students’ capacity for meaning-making across modes. Multiple, complementary modes of representation help learners process English materials more easily, retain new vocabulary, express ideas with greater confidence, and take a more active role in classroom interaction, provided that media selection and task design are carefully aligned with learning goals and proficiency levels. Overall, the study positions multimodal learning not merely as media variation, but as a pedagogical strategy that supports more comprehensive and context-sensitive language acquisition in EFL settings.